2001
DOI: 10.1097/00019605-200107000-00008
|View full text |Cite
|
Sign up to set email alerts
|

De novo interstitial long arm deletion of chromosome 3 with facial dysmorphism, Dandy-Walker variant malformation and hydrocephalus

Abstract: We report an 8-year-old girl with coarse facial features, macrocrania and developmental delay. Cranial anomalies in the form of hydrocephalus and Dandy-Walker (DW) variant malformation were detected on neuro-imaging. Karyotyping revealed a de novo interstitial deletion of bands 3q25.1 to 3q25.33. Deletion of the 3q24-q26 region appears to be associated with a somewhat similar constellation of findings of craniofacial dysmorphism (broad and depressed nasal bridge and low set posteriorly rotated ears), mental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
3
8
0
2
Order By: Relevance
“…The four highly signiWcant MABs 3q26.1, 3q26.2 and 3q26.3 (P < 0.001) and 3q25 (P < 0.01, P > 0.001) (clinical descriptions (Sudha et al 2001;Willner et al 1990)) are likely to represent a single locus; indeed, an association of 3q deletions (3q24.3-q25.33) and DWM has been previously shown. ZIC1 and ZIC4 have been suggested as possible causative genes (Grinberg et al 2004).…”
Section: Discussionmentioning
confidence: 83%
“…The four highly signiWcant MABs 3q26.1, 3q26.2 and 3q26.3 (P < 0.001) and 3q25 (P < 0.01, P > 0.001) (clinical descriptions (Sudha et al 2001;Willner et al 1990)) are likely to represent a single locus; indeed, an association of 3q deletions (3q24.3-q25.33) and DWM has been previously shown. ZIC1 and ZIC4 have been suggested as possible causative genes (Grinberg et al 2004).…”
Section: Discussionmentioning
confidence: 83%
“…Vertical black lines indicate the position of FOXL2 gene (causative of BPES), and ZIC1-ZIC4 genes, as indicated. *previously described by Sudha et al [26]; **previously described by Ko et al [23]. …”
Section: Resultsmentioning
confidence: 99%
“…We observed a 3q24 deletion in a patient (case 5) with developmental delay, imperforated anus, and cleft palate. Deletion of the 3q24-q26 region including the Dandy-Walker malformations (DWM) critical region (3q24) appears to be associated with a somewhat similar constellation of findings including craniofacial dysmorphism (broad and depressed nasal bridge and low set posteriorly rotated ears), mental retardation, congenital heart defects, and central nervous system malformations [26]. A previous study reported the critical region associated with DWM, which encompasses the ZIC1 and ZIC4 genes, by mapping the 3q24 interstitial deletions in several individuals with DWM [27].…”
Section: Discussionmentioning
confidence: 99%